Minor allele of rs55763075 located in MTHFR is associated with the risk of cognitive impairment after anesthesia via modulating miR-34b - Si-ying Li (Nature Portfolio, 2021)
Abstract This study aimed to investigate the association between cognitive impairment after general anesthesia and rs55763075 polymorphisms. We enrolled and grouped patients undergoing general anesthesia according to their genotypes of rs55763075 polymorphism. Mini–Mental State Examination (MMSE) scoring was performed to evaluate the cognitive status of patients. Quantitative real-time PCR was carried out to analyze the expression of methylenetetrahydrofolate reductase (MTHFR) mRNA and miR-34b while Western blot was performed to evaluate the expression of MTHFR protein. Furthermore, we studied the effect of rs55763075 polymorphism on the expression of MEHFR via luciferase assay. Accordingly, we found that the MMSE score in GG/GA groups was significantly higher than that in AA group. And a significant reduction of MTHFR mRNA expression was observed in the serum and peripheral blood mononuclear cells (PBMCs) of patients carrying AA genotype compared with the patients carrying GG/GA genotypes. Moreover, the MTHFR expression was much lower in the cultured AA-genotyped cells transfected with miR-34b. Luciferase assay results also showed that miR-34b transfection reduced luciferase activity in the cells carrying A allele but not in cells carrying G allele. In summary, the data of this study showed that minor allele (A) of rs55763075 polymorphisms in the 3'-untranslated region of MTHFR mRNA generated a potential binding site for miR-34b, which led to reduced level of folic acid in the patients carrying the AA genotype. Furthermore, we found that the MMSE score of AA-genotyped patients was lower than that of patients carrying GG/GA genotypes.